PENGARUH KEPEMIMPINAN ETIS TERHADAP KELELAHAN EMOSIONAL DENGAN WORK AUTONOMY SEBAGAI VARIABEL MEDIASI PADA KANTOR WILAYAH BKKBN PROVINSI RIAU - Rabiah Mayang Sari; Karmila Sari; Hardi (Indragiri Research Center (ingreat), 2025)
This study aims to examine the effect of ethical leadership on emotional exhaustion with work autonomy as a mediating variable at the Regional Office of the National Population and Family Planning Agency (BKKBN) of Riau Province. Emotional exhaustion, which is often influenced by work environment factors, can have a negative impact on individual well-being and organizational performance. On the other hand, ethical leadership implemented by leaders can create a more supportive work environment, which allows employees to have autonomy in working, and in turn can reduce the risk of emotional exhaustion. This study uses a quantitative method with a survey approach at the Regional Office of the BKKBN of Riau Province. The results of the study indicate that ethical leadership significantly influences emotional exhaustion, both directly and through the mediation of work autonomy. This study provides important insights for organizational leaders in designing leadership strategies that can improve employee well-being and prevent emotional exhaustion.